Pharmacokinetics and Tissue Distribution of Enrofloxacin Following Single Oral Administration in Yellow River Carp (Cyprinus carpio haematoperus) - Yang, Fan; Zhang, Chao-Shuo; Duan, Ming-Hui; Wang, Han; Song, Zhe-Wen; Shao, Hao-Tian; Ma, Kai-Li; Yang, Fang (Frontiers in Veterinary Science, 2022)
The pharmacokinetics and tissue distribution of enrofloxacin were determined in Yellow River carp (Cyprinus carpio haematopterus) reared at 20 °C after single oral administration of enrofloxacin at 10 mg∙kg-1 body weight. Plasma, bile, and different tissue samples, including liver, kidney, gill, gut, and skin-muscle, were collected at predetermined times points. An HPLC method was developed to simultaneously determine the concentrations of enrofloxacin and its metabolite, ciprofloxacin. However, ciprofloxacin was only detectable in some liver samples with trace levels. Then the average enrofloxacin concentrations versus time data were subjected to a non-compartmental analysis using WinNonLin 5.2 software. Multiple peaking profiles were observed in all enrofloxacin concentration-time curves. The peak concentration (Cmax) values were observed as 0.79, 1.01, 2.09, 2.85, 4.34, 10.78, and 13.07 μg∙mL-1 (or g-1) in plasma, skin-muscle, gill, kidney, liver, bile, and gut, respectively, and the corresponding time to reach peak concentration (Tmax) was 8, 8, 1, 8, 1, 72, and 4 h, respectively. The values of elimination half-life (T1/2λZ) of enrofloxacin in different tissues was in the following order: gill (291.13 h) > liver (222.29 h) > kidney (157.22 h) > plasma (129.44 h) > gut (91.47 h) > skin-muscle (87.77 h) > bile (86.22 h). The present results showed that enrofloxacin had a wide distribution in different tissues, however slow absorption and elimination in Yellow River carp. Additionally, enrofloxacin exhibited large distribution in bile, indicating that bile excretion might be the primary elimination route of enrofloxacin in Yellow River carp. A withdrawal period was calculated as 379.2 °C-day for single oral dosing of enrofloxacin at 10 mg/kg body weight. Based on the calculated PK/PD indices of AUC/MIC or Cmax/MIC, the current enrofloxacin dosing regimen might have a positive therapeutic effect on the infection of Flavobacterium columnare, Aeromonas sobria, or Aeromonas hydrophila. However, the depletion study following multiple oral doses should be carried out in Yellow River carp reared at lower temperatures, and the withdrawal period should also be further calculated.